Infectious Burden and Cognitive Decline in the Northern Manhattan Study. Issue 8 (20th August 2015) - Wright, Clinton B.; Gardener, Hannah; Dong, Chuanhui; Yoshita, Mitsuhiro; DeCarli, Charles; Sacco, Ralph L.; Stern, Yaakov; Elkind, Mitchell S. V.
Abstract : Objectives: To determine whether infectious burden (IB) is associated with worse performance and decline on a battery of neuropsychological tests. Design: Prospective cohort study (Northern Manhattan Study (NOMAS)). Setting: Community. Participants: A subsample of 588 stroke‐free NOMAS participants with IB and cognitive data (mean age 71 ± 8, 62% female, 14% white, 16% black, 70% Hispanic) and 419 with repeat cognitive testing. Measurements: Samples used for IB data were collected at baseline. Two waves of neurocognitive assessments occurred during follow‐up. Participants underwent a neuropsychological battery and had repeated testing (mean time span 6 ± 2 years). Using factor analysis–derived domain‐specific Z scores for language, memory, executive function, and processing speed, associations between a quantitative stroke risk‐weighted IB index (IBI), based on five common infections ( Chlamydia pneumoniae, Helicobacter pylori, cytomegalovirus, herpes simplex viruses 1 and 2), and cognitive performance and decline in each domain was examined. Results: Adjusting for demographic characteristics, socioeconomic status, crystallized cognitive abilities, and vascular risk factors, the IBI was inversely associated with executive function at baseline (beta = −0.10, P  = .01) but not with baseline language, memory, or processing speed performance in adjusted analyses. The IBI was associated with cognitive decline in the memory domain, adjusting for demographic and vascular risk factors ( P  = .02). Conclusion: A quantitative stroke risk‐weighted measure of IB explained variability in baseline executive function performance and associated with decline in memory. Past exposure to common infections may contribute to vascular cognitive impairment and warrants further study.